Boole's strategy in multistep block method for Volterra integro-differential equation - Baharum, N. A.; Majid, Z. A.; Senu, N. (UPM Press, 2022)
This article presents a numerical approach for solving the second kind of Volterra integro- differential equation (VIDE). The multistep block-Boole's rule method will estimate the solutions for the linear and nonlinear problems of VIDE. The method computes two solutions for VIDE along the interval. The proposed method is developed by derivation of the Lagrange interpolating polynomial. The convergence and stability analysis of the derived method are discussed. From the perspective of total function calls and time-saving, the computation results explained that the derived method performs better than other existing methods.